(untitled) (Journal of Comparative & International Higher Education, 2022)
The future of international education and academic exchange is bright. This is not because the world turned out to be flat or that globalization was a good tide that lifted all ships. Instead, there is something in the human spirit from the earliest days of Plato’s Academy that appears to prefer in-person contact and a location outside of one’s home to spur academic thinking and collaboration. And despite the fact that the word “virtual” transformed from an adverb into a noun since the start of the COVID-19 pandemic, there is indication that as soon as it is safe for students and faculty to return to in-person learning on campuses and in classrooms, that is what they intend to do.